2011
DOI: 10.1093/infdis/jiq138
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Raltegravir Intensification in Antiretroviral-treated, HIV-infected Patients with a Suboptimal CD4+ T Cell Response

Abstract: NCT00631449.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
118
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(141 citation statements)
references
References 46 publications
19
118
1
3
Order By: Relevance
“…[36][37][38][39] However, none of these studies was placebo-controlled, and subjects often improve their ART adherence when entering clinical trials, which may have explained the reduction in low-level viremia experienced by placebo-treated subjects in our own trial and in another recently reported intensification study. 40 The apparent reduction in T-cell activation during maraviroc intensification reported in the uncontrolled AIDS clinical trials group study (A5256) was also primarily driven by declines in CD38 expression, whereas HLA-DR expression actually increased significantly (which is largely consistent with our results), and neither of those changes were confirmed when retesting cryopreserved PBMCs from that trial. 36 The only other placebo-controlled trial of maraviroc intensification did not find any evidence for a difference in T-cell activation between placebo-and maraviroc-treated subjects, although final results have not yet been published.…”
Section: Discussionsupporting
confidence: 87%
“…[36][37][38][39] However, none of these studies was placebo-controlled, and subjects often improve their ART adherence when entering clinical trials, which may have explained the reduction in low-level viremia experienced by placebo-treated subjects in our own trial and in another recently reported intensification study. 40 The apparent reduction in T-cell activation during maraviroc intensification reported in the uncontrolled AIDS clinical trials group study (A5256) was also primarily driven by declines in CD38 expression, whereas HLA-DR expression actually increased significantly (which is largely consistent with our results), and neither of those changes were confirmed when retesting cryopreserved PBMCs from that trial. 36 The only other placebo-controlled trial of maraviroc intensification did not find any evidence for a difference in T-cell activation between placebo-and maraviroc-treated subjects, although final results have not yet been published.…”
Section: Discussionsupporting
confidence: 87%
“…This suggests that treatment intensification adding more drugs to current treatment regimens may not help to reduce the size of the latent reservoir or eradicate the virus. This is consistent with a number of clinical trials in which addition of new drugs such as the integrase inhibitor raltegravir did not reduce persistent low-level viremia in patients with HIV suppression during combination antiretroviral therapy [5,18,22,23,28,53]. It also agrees with our recent results of using a multi-stage model to study the dynamics of 2-LTR (long terminal repeat) circles, a marker of recent viral infection [52].…”
Section: Discussionsupporting
confidence: 92%
“…usRNA can be easily detected with a seminested or nested quantitative reverse transcription PCR (qRT-PCR) (36-39) or by ddPCR, using a set of primers and probe against Pol or Gag (17, 30, 33, 39). Alternatively, some investigators have adapted commercial quantitative tests for HIV-1 plasma viremia, such as Amplicor (Roche Diagnostics) (40,41) or APTIMA HIV-1 Qualitative assay (Hologic) (42,43) for the quantitation of caRNA. msRNA primers are designed to amplify a region containing the Tat/Rev (or Tat/Nef) exon-exon junction and can be quantified by nested qRT-PCR (36, 38, 39) or ddPCR (17,39,44).…”
Section: Pcr-based Assays To Measure the Latent Reservoirmentioning
confidence: 99%